PENERAPAN PEMBELAJARAN MATEMATIKA REALISTIK DENGAN TIPE THINK PAIR SHARE UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII SMP NEGERI 2 KOTA BENGKULU - Effie Efrida Muchlis; Pipin Devi Erasanti; Maizora Syafdi; Sulistiawati Sulistiawati; Nadya Rahma Syabira (Journal on Mathematics Education Research (J-MER), 2022)
Learning mathematics more often uses expository methods that are teacher-oriented which does not provide opportunities for students to construct their own mathematical ideas so that students become passive learners. Student confused about using mathematical concepts because students only memorized concept is not understanding it. This study aims to find out how apply Realistic Mathematics Learning (PMR) with Think Pair Share (TPS) so that there is an increase in activities and learning outcomes of mathematics. Type The research carried out is Classroom Action Research (PTK) with data collection techniques through student activity observation sheets and test results study. The subjects in this study were class VIIIB students of SMP Negeri 2 Bengkulu City. The results of this study indicate the application of Mathematics Learning Realistic (PMR) with Think Pair Share (TPS) type can improve activities and student learning outcomes of mathematics. Student activity is enhanced with giving contextual problems, proper group division, giving value add to the group that is ready to advance at the presentation. Enhancement student learning outcomes can be seen from the increase in the average value of students from cycle I up to the third cycle, namely: 74.48; 79.44; 83.16 with the proportion of mastery learning classical from cycle I to cycle III, namely: 58.33%; 77.78%; 86.11% and power student absorption from cycle I to cycle III is: 74.48%; 79.44%; 83.16%.